THE ARAB SPRING ONLINE NEWS COVERAGE: CORPUS-BASED ANALYSIS OF THE TUNISIAN AND EGYPTIAN REVOLUTION KEYWORDS - Muhammad Marwan Ismail; Farah Nadia Harun; Wan Moharani Muhamad; Nurhasma Muhamad Saad; Zulkipli Md Isa, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
In 2011, the Arab world had become the centre of attention once again after the emergence of the so-called ‘Arab Spring’ in December 2010. This historical event in the modern history of the Arab region has brought significant social and political reform to the Arab world. The wave of Arab uprising begins in Tunisia at the end of 2010, rapidly separated into other neighbouring countries such as Egypt, Libya, Morocco, Syria, Bahrain, and Sudan. Since the early stage of protest, which mainly participated by locals, mass media has comprehensively reported this historical event, which brought down many Arab leaders in power for decades. Thus, Arab Spring has become the headline of many international media outlets, and the media are still discussing the significant impact of the event until now. Hence, the main objective of the study is to examine the event's Arabic online news discourse by focusing on the keywords and prominent social actors in the news reports surrounding the Arab Spring. This will indicate what has been included and excluded or highlighted and marginalised in the news coverage. The data is consist of Modern Standard Arabic (MSA) online news published by four prominent news outlets namely with different origin and background: Al-Arabia of Saudi Arabia, Al-Jazeera of Qatar, BBC Arabic of the UK and CNN of the USA. These well-established news outlets were selected for their comprehensive international coverage aims at various Arabic readers worldwide. The study employs corpus linguistics analytical tools by using corpus data mining software ‘AntConc 3.4’. Then, the quantitative results of corpus data will be analysed using a qualitative approach based on the textual-oriented Critical Discourse Analysis (CDA) of Fairclough (1992) and Wodak (2001). The result shows that news coverage of the event has highlighted several keywords that indicate the main social actors and main social events of the Arab Spring. These keywords are the shared command features among the news outlets, although each outlet portraying them is significantly different. Finally, the article presents suggestions for other related studies in the future.